Trends of Erythrocyte Alloimmunization in Transfused Women - Ghaffar, Sunia; Uddin, Nasir; Ghaffar, Samia; Haq, Hala; Nawab, Izza; Ghaffar, Bushra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To identify the trends of red cell alloimmunization in multi-transfused females using red blood cell panels.Study design: Cross-sectional study.Place and Duration of Study: Army Medical College and Armed Forces Institute of Transfusion with the collaboration of Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Aug 2018.Methodology: Blood samples of 75 females with prior history of blood transfusion were collected from Pak Emirates Military Hospital, Rawalpindi Pakistan, selected by a non-probability consecutive sampling technique. After pilot diagnostic tests for ABO and Rh D blood grouping, samples were screened by three cell panels to identify the presence of RBCs alloimmunization. Positive results were further recognized by 11 cell panels.Results: Seventy-five women with a history of at least one blood transfusion were selected for the screening of red cell alloimmunization. The frequency of alloantibodies in transfused women was 1(1.3%). The only alloantibody identified was anti-e, which was a rare alloantibody.Conclusion: Study confirmed that Rh alloantibodies are the most prevalent antibodies, regardless of age, ABO blood grouping, Rh grouping and ethnicity. Our study also confirmed that multiple transfusions are associated with the development of red cell alloimmunization.